2022
DOI: 10.1134/s2079057022030109
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation of Post-Stroke Patients with Motor Function Disorders: A Review

Abstract: Stroke is the main reason for disabilities of increasing geriatric population. It affects brain and motor function domains significantly reducing the life quality. Recent coronavirus pandemic raised a question on changing approaches to deliver post-stroke rehabilitation services to geriatric patients due to their high risk of serious illness. This paper presents an overview of current telerehabilitation approaches for motor function recovery and balance training of post-stroke patients. We used papers from pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…This approach is in line with the WHO 2030 strategy to increase rehabilitation and utilize technology to address the global shortage of rehabilitation professionals. Our findings are in agreement with recently published reviews that found telerehabilitation using different tools can be effective for stroke patients' rehabilitation [33,34,60]. On the other hand, some reviews reported weak evidence for using TR in stroke management [57,58].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This approach is in line with the WHO 2030 strategy to increase rehabilitation and utilize technology to address the global shortage of rehabilitation professionals. Our findings are in agreement with recently published reviews that found telerehabilitation using different tools can be effective for stroke patients' rehabilitation [33,34,60]. On the other hand, some reviews reported weak evidence for using TR in stroke management [57,58].…”
Section: Discussionsupporting
confidence: 93%
“…Stroke patients, who typically have high rates of co-morbidity (for example, hypertension and diabetes mellitus), have experienced reduced and lower-quality healthcare services during the pandemic period of COVID-19, from delayed acute medical responses to delayed, canceled, or reduced rehabilitation appointments, especially for people who live in remote areas. Consequentially, there was a trend toward searching for a new tool of rehabilitation to overcome such risks and barriers [32][33][34]. Telerehabilitation using different models of extended reality provides a good solution to the need for a regular practice that helps patients obtain their rehabilitation services either with the supervision (synchronous) [35] or without the supervision (asynchronous) [36] of their therapists.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews have been conducted on the applications of AI in the rehabilitation of different populations 8 , 10 , 18 , 19 , 44 46 as well as VRehab or telerehabilitation 9 , 47 50 . None of the published literature has addressed the combined role of AI and VRehab to support patient recovery in various rehabilitation populations.…”
Section: Introductionmentioning
confidence: 99%